Secreted EMC10 is upregulated in human obesity and its neutralizing antibody prevents diet-induced obesity in mice - Xuanchun Wang; Yanliang Li; Guifen Qiang; Kaihua Wang; Jiarong Dai; Maximilian McCann; Marcos D. Munoz; Victoria Gil; Yifei Yu; Shengxian Li; Zhihong Yang; Shanshan Xu; et al. (Nature Communications, 2022)
Secreted isoform of endoplasmic reticulum membrane complex subunit 10 (scEMC10) is a secreted protein of incompletely understood physiological function. Here the authors show that scEMC10 is upregulated in people with obesity, and that that genetic EMC10 deletion or antibody-based neutralization of EMC10 prevents diet-induced obesity in mice.